On Defrosting - Ruiz, Jeanette (Satura, 2022)
I was once full. Hands caressed my handles at the very least three times a day. Although they touched only to use, I still enjoyed their warmth. My insides were cold, especially my brain... actually... it was frozen. I suffered from an eternal state of brain freeze, stuck in one place, constantly repeating the tasks of yesterday. The only talent I knew was how to preserve things, how to keep them alive, well, at least until they went bad. At times whole worlds were growing, blooming, evolving within me. Sometimes I’d keep things in for years. The stench wouldn’t reveal itself until the lid was lifted, the pressure often threatening to explode the cover. Still, I fed the restless hands that touched me. They were always opening and closing me, putting things in and taking things out. At times, late into the night, hungry eyes gazed deep inside of me longing for something unknown.